Social and Cultural Black Adjustment of Afro-Caribbean People in the United Kingdom from the Post World War II up to the Present Time - Belaid, Hafsa (My University, 2017)
The fact that Britain nowadays a multicultural and a multiracial society is an indisputable reality. This is mainly the outcome of successive waves of immigrants from the new Common Wealth countries. History has witnessed the extraordinary changes and development from slaves and mere ‘accessories’ and ‘Chattel’ to full British citizens. Their extraordinary journey in Britain has been full of suffering and hardship, their ever lasting struggle against persisting white racism has been the proof of their courage and greatness.In addition to old settled communities of black people who came as a result of the slave trade, other Caribbean and African people came to Britain during the wars to help for the war effort and to fight for their mother country. They were joined by greater waves of immigrants after the war to help Britain reconstruct its economy and to fill the acute labour shortage that it was facing. All of them came hoping for better lives and recognition, yet all they found was huge racism. Their disillusionment had been great indeed. They were given jobs with menial functions, low paid and might shifts that white people did not want. They faced daily discrimination in housing, education and work. They were frequently confronted to color bars in public places and were harassed in the streets. At different occasions, they had been the target of the racist attack performed by white youths in violent riots.Today, black people are integrant part of the British society. They have completely changed the face of Britain, changing it from an exclusively white society to a multiracial one. Over time their communities have largely expanded. The successive waves of Afro-Caribbean people have brought about irreversible changes to the British culture, geography and society. Their presence has altered the meaning of ‘Britishness’. Every aspect of British life, whether political, cultural or social, has been influenced by the black culture.In spite of the challenges that they are still facing, a great improvement has been made since the post war period. A number of them have managed to achieve great fame and success, and most of all recognition and are celebrated worldwide.
Keywords: Afro-Caribbean; Britain; Social and Cultural Adjustment; Racism issues; British multiculture